2020
DOI: 10.3389/fnmol.2020.00116
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Against Oxidative Stress: Phytochemicals Targeting TrkB Signaling and the Nrf2-ARE Antioxidant System

Abstract: Oxidative stress (OS) plays a critical role in the pathophysiology of several brainrelated disorders, including neurodegenerative diseases and ischemic stroke, which are the major causes of dementia. The Nrf2-ARE (nuclear factor erythroid 2-related factor 2/antioxidant responsive element antioxidant) system, the primary cellular defense against OS, plays an essential role in neuroprotection by regulating the expressions of antioxidant molecules and enzymes. However, simultaneous events resulting in the overpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 151 publications
(210 reference statements)
0
102
0
3
Order By: Relevance
“…Oxidative stress (OS) is a pathological condition that develops when the production of reactive oxygen species (ROS) reaches an excessive level with lower efficiency of the cellular antioxidant defense system [ 40 ]. Factors contributing to OS in the brain include excitotoxicity, depletion of the cellular antioxidant system, high susceptibility to lipid peroxidation, and high oxygen demand [ 41 ].…”
Section: Pathophysiology Of Brain Disordersmentioning
confidence: 99%
“…Oxidative stress (OS) is a pathological condition that develops when the production of reactive oxygen species (ROS) reaches an excessive level with lower efficiency of the cellular antioxidant defense system [ 40 ]. Factors contributing to OS in the brain include excitotoxicity, depletion of the cellular antioxidant system, high susceptibility to lipid peroxidation, and high oxygen demand [ 41 ].…”
Section: Pathophysiology Of Brain Disordersmentioning
confidence: 99%
“…Nrf2 binding with the antioxidant responsive element (ARE) leads to the transcriptional activation of downstream genes such as NAD(P)H: quinone oxidoreductase (NQO1), glutathione-S-transferase (GST), and hemeoxygenase-1 (HO-1) [ 27 , 30 , 31 , 32 ]. Moreover, several studies have shown that overexpression of Nrf2 produces a protective effect against oxidative stress [ 18 , 33 , 34 , 35 ]. Recently, the activation of inflammatory markers and apoptotic pathways in the pathogenesis of neuropathic pain has been demonstrated [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in p-Akt also affects the reduction of the antioxidant system’s ability to eliminate ROS and oxidative stress [ 72 ]. p-Akt increases the expression of Nrf2 from Kelch-like, ECH-associated protein 1 (keap1), and the generated Nrf2 increases the expression of HO-1, NAD(P)H quinone oxidoreductase (NQO1), and SOD protecting the antioxidant system [ 76 ]. However, a decrease in p-Akt inhibits the normal function of the neuronal survival pathway, and accumulated oxidative stress leads to neuronal cell death [ 72 ].…”
Section: Discussionmentioning
confidence: 99%